Problematika Kejaksaan Negeri Pekanbaru Dalam Mengeksekusi Uang Pengganti Terpidana Tindak Pidana Korupsi - Tri Novita Sari Manihuruk (Jurnal Selat, 2021)
The criminal execution of paying replacement money becomes a problem when the prosecutor as the executor will carry out the execution. The facts on the ground show that many convicts do not pay replacement money. The problems of the Pekanbaru District Attorney's Office in carrying out the execution of replacement money for convicted criminal acts of corruption are: First, the convict does not pay the replacement money charged to him; and the convict does not have sufficient property to pay the replacement money. Second, there is no synergy between the Ministry of Finance and the Pekanbaru District Attorney if the convict does not pay the replacement money. The efforts of the Pekanbaru District Prosecutor's Office in Executing Replacement Money Against Corruption Convicts, namely asset tracing (asset tracking), and increasing synergy between the Ministry of Finance and the Pekanbaru District Attorney if the convict does not pay the replacement money.